Young and older workers: competence, performance and trainability - Hashim, Junaidah (2011)
Purpose - This study examines the performance of young and older civil servants, specifically how effective and efficient they are in performing their duties and responsibilities. It also aims to investigate the workers’ competence and trainability. Methodology – A survey method was applied in this study. The questions were adapted from Rothwell (2002) and Sarmiento et al. (2007) for performance and competence respectively, while trainability measurements were adapted from Maurer et al. (2008). The sample size of 618 respondents involved 51.3% older workers and 48.7% young employees. Findings – The employees’ self-assessments revealed that the older workers found themselves more competent, perform better and more trainable than their young counterparts. However, there is no significant different between the older workers and young employees in their superiors’ assessment. The findings also showed that the performance of employees is contributed by their competence and trainability. Research implication – It would be interesting to include older workers from other sectors because the education sector is perceived to be less physically demanding, also to examine the mutual learning and group behaviour of the young workers with the old ones. Practical implication – It provides valuable insights into training for older workers. It is worth to extend the retirement age of the older workers as they were found to be competent, well performers and are trainable. Originality / Value – This study obtained data from two sources: employees’ self-assessment and superior assessment.